DEATH AS THE “REAL”: A PSYCHOANALYTIC READING OF MATTHEW ARNOLD’S YOUTH AND CALM - Alexei Wahyudiputra (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Matthew Arnold was one of the poets who paid special attention to youth and the dynamics of youth culture in the Victorian era. Living in an era that stimulated modern times, Arnold produced writings that can be classified as historical records, although not factual, of society's reactions to the fundamental social and cultural changes of the time. The literary arena was particularly affected, as the Victorian era marked the beginning for poets and artists alike to shed the romantic spirit that they had breathed into their works and adapt to the technological and industrial realities around them. This article explores Matthew Arnold's poem entitled “Youth and Calm”. The poem explores a stream of consciousness that contemplates “the youth